IMPROVEMENT OF COMMUNICATIVE COMPETENCES AND ASSESSING SPEAKING THROUGH UTILIZING FLIPGRID - Xushmamatova Aminaxon Rustam qizi (American Journals Publishing, 2024)
Integrating innovative methods in assessing language ability of learners are critical part of language teaching and learning. The present paper is dedicated to explore integration of digital platform “Flipgrid” where instructor posted tasks and students answer in video format. This innovative tool allowed to process students learning about the content. Students recorded videos were peer and self-assessed with follow-up teacher’s feedback relying on rubric (Grammar and Vocabulary, Discourse Management, Pronunciation, Interactive Communication). After the implementation of Flipgrid, subjects were asked to take a survey on benefits of Flipgrid where most of them highlighted the advantageous as the tool allowed them to be a part of assessment process and to be aware of areas that needs improvement in their oral proficiency.
Keywords: “Flipgrid”, interactive communication, Communicative competence, digital platform